Effect Of Job Dimensions On Repatriates’ Career Ambition, Career Expectation And Work Adjustment In GCC - Al Jofan, Ali (2023)
This study is founded on the notion that student repatriates’ work adjustment is influenced by job dimensions set out in the Framework of International Adaptation. Generally, student repatriates expect effortless transitions prior to adjustment to the work environment. Their career ambitions and career expectations regarding their future careers might be affected by the job dimensions once they transfer to workplaces. Thus, understanding the factors that impact the adjustment process is necessary. This research is important for investigating how Gulf Cooperated Council (GCC) countries, as developing nations, encourage their students to pursue qualifications abroad, particularly in higher education.